2005
DOI: 10.1007/s00467-004-1790-8
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate treatment of pediatric fracture patients on chronic steroid therapy

Abstract: Pediatric nephrology and rheumatology patients with steroid-induced osteopenia are at risk of skeletal fracture. Bisphosphonate therapy has not been routinely advocated as a primary or secondary intervention for steroid-associated fractures in this population. This case control study evaluates the role of pamidronate therapy as a secondary fracture intervention. Children with symptomatic pathological fractures of the axial spine or ribs were treated with pamidronate 1 mg/kg/dose (n=17) IV at 60-day intervals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…Leonard et al recently reported that intermittent GC therapy resulted in similar spine and total-body BMC in children with SSNS compared with controls [6], suggesting that bone mass is relatively preserved. However, Acott et al [14] reported vertebral fractures among NS children within 3 months of receiving GCs. Our report further supports the observation that vertebral body strength can indeed be compromised with intermittent GC therapy for NS.…”
Section: Discussionmentioning
confidence: 99%
“…Leonard et al recently reported that intermittent GC therapy resulted in similar spine and total-body BMC in children with SSNS compared with controls [6], suggesting that bone mass is relatively preserved. However, Acott et al [14] reported vertebral fractures among NS children within 3 months of receiving GCs. Our report further supports the observation that vertebral body strength can indeed be compromised with intermittent GC therapy for NS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reductions in lumbar spine areal bone mineral density (LS BMD) have been documented during the initial high-dose GC treatment phase in children with NS [9,10], and modest deficits in LS bone mineral content have been shown following years of intermittent GC therapy for steroid-sensitive disease [11]. Overt bone fragility manifesting as vertebral fractures has also been reported in children with NS following the initial GC treatment phase in the context of a treatment study [10], and later in the disease course [12].…”
Section: Introductionmentioning
confidence: 94%
“…Overt bone fragility manifesting as vertebral fractures has also been reported in children with NS following the initial GC treatment phase in the context of a treatment study [10], and later in the disease course [12]. However, the frequency and characteristics of vertebral deformities in pediatric NS as well as their relationship to clinical factors has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…123,[125][126][127] Pilot studies have also been conducted in adolescents with anorexia nervosa. 128 In osteogenesis imperfecta, an openlabel study examining the use of cyclic administration of intravenous pamidronate reported reduced pain and fractures associated with dramatic increases in BMD.…”
Section: Bisphosphonatesmentioning
confidence: 99%